GNAS Mutations in Fibrous Dysplasia: A Comparative Study of Standard Sequencing and Locked Nucleic Acid PCR Sequencing on Decalcified and Nondecalcified Formalin-fixed Paraffin-embedded Tissues. Issue 9 (October 2016) - Jour, George; Oultache, Alifya; Sadowska, Justyna; Mitchell, Talia; Healey, John; Nafa, Khedoudja; Hameed, Meera
Abstract : It is well known that fibrous dysplasia (FD) is characterized by the presence of activating mutations involving G-nucleotide binding protein-α subunit ( GNAS ) involving codon R201 and rarely codon 227 with a mutation frequency between 45% and 93%. Herein, we investigate the sensitivity of detection of GNAS mutations in exons 8 and 9 using a standard and a highly sensitive locked nucleic acid polymerase chain reaction (LNA-PCR) sequencing in 52 cases of FD. In view of the recent report of GNAS mutations in a small number of low-grade osteosarcomas, we also tested in addition 12 cases of low-grade osteosarcomas. GNAS exon 8 mutations p.R201H (31%), p.R201C (15%), and p.R201S (2%) were identified in 50% of FD cases. LNA-PCR sequencing identified only 1 positive case within the mutation negative cases tested by standard PCR and Sanger sequencing. No mutations were identified in any of the low-grade osteosarcomas by standard and LNA-PCR sequencing. There was no association between age, site, size, specimen type, and mutational status. No exon 9 or codon 227 mutations were identified in any of tested cases. There was a significant difference in the sensitivity of the assay between decalcified and nondecalcified FDs (31% vs. 70%, P =0.002). LNA-PCR has no added value in enhancing detection sensitivity for GNAS mutations in FD. In addition to decalcification, innate somatic mosaicism contributes to the decreased sensitivity in mutation detection.